An historic theropod-dominated track assemblage from the Upper Jurassic of Sichuan, China. (2nd November 2021) - Xing, Lida; Lockley, Martin G.; Romilio, Anthony; Klein, Hendrik; Peng, Guangzhao; Persons, W. Scott; Ye, Yong; Jiang, Shan; Wang, Miaoyan
ABSTRACT: A Late Jurassic ichnofauna from the Suining Formation at the Yejipo site, Huangba Village, Sichuan Province has been locally known for its fossil footprints since the 1980s as the name 'Yejipo', meaning feral chicken/pheasant indicates. The best-preserved trackway represents a large theropod (mean footprint length 55.0 cm) assigned to Megalosauripus isp, with a length/width ratio of 1.4, and mesaxony index of 0.31. The tracks show the digit III/footprint length ratio of 0.60 typical of this ichnogenus. Two consecutive right footprints reveal an unusual digital pad trace pattern, exclusive of digit II metatarsal phalangeal pad giving a pad formula of 3-3-4 corresponding to digits II-III-IV rather than the typical 2-3-4 formula of theropods. As this formula can only be observed in the right, not the left, footprints, it is possible to suggest a pathological or congenital deformity. The assemblage also includes a typical elongate Grallator track (footprint length 13.8 cm, length/width 1.9). Other small tridactyl tracks are provisionally assigned to the ichnogenus Anomoepus . Collectively the ichno-assemblage is similar to others known from the Jurassic of China, although the occurrence of an anomalous Megalosauripus track is unusual.